Polyphenols analysed by UHPLC-ESI-MS/MS and antioxidant activities of molasses, acorn and leaves of oak (Quercus robur subsp. pedunculiflora) - Bursal, Ercan; Boğa, Remzi (Mattioli 1885, 2018)
Objectives: The leaves of oak trees have been boiled in water and the extracts have been evaporated to produce oak molasses. Colloidal precipitants have been widely used as dietary molasses since have very effective antiseptic functions as alternative medicine for ages in some parts of the world. Present study aimed to investigate the biological activities of oak products for elucidating the scientific basis of alternative medicine. Thus, antioxidant activities of ethanol and water extracts of acorn, leaves and molasses of oak trees (Quercus robur subsp. pedunculiflora) were evaluated. Results: We determined antioxidant activities of extracts by different in vitro methods including DPPH free radical scavenging, ABTS+ radical scavenging, total antioxidant activity determination by ferric thiocyanate method, reducing power by FRAP methods, separately. The results were compared with BHA, BHT and ascorbic acid as standard antioxidant compounds. The acorn seed extract, which presented the highest antioxidant potential, was the most effective scavenger against DPPH free radical. Also, phenolic compounds of the molasses were identified by UHPLC-ESI-MS/MS. The highest phenolic compound was quinic acid (4556 ± 219 ppb). Conclusion: Acorns and leaves of oak trees (Quercus robur subsp. pedunculiflora), as well as traditional oak molasses" have high antioxidant potential for the food industry as a food ingredient to produce functional food products. © Mattioli 1885.
Keywords: Acorn; Antioxidant; LC-MS/MS; Nutrition; Phenolic acid; Quercus